Female Migration and Child Occupation in Rural El Salvador - Acosta, Pablo (2012)
This article looks at the consequences of migration in terms of child education and child labor using a unique rural panel dataset for El Salvador. Results suggest gender differences in the consequences of migration on child activities that remain in El Salvador. While female migration tends to reduce child labor, both in domestic and non-domestic activities, male migration seems to stimulate it, in particular in terms of domestic labor. In contrast, while male migration has null or slightly positive impact in terms of school enrollment rates, female migration apparently reduces the likelihood that a particular child stays at school. Some of these results differ according to the gender of the child. The results do not seem to be driven by female migrants remitting more than males, but rather to alternative competing explanations, such as the existence of child-adult male labor substitution, differences in the use of remittances by gender of the recipient person, or limited ability to monitor funds when remitted by female migrants.